Consumo de alcohol y sustancias psicoactivas en adolescentes mestizos e indígenas del cantón Catamayo de la provincia de Loja. - Ojeda Guerrero, Diana Elizabeth (2017)
The research is done in order to describe the beginning of alcohol consumption and psychoactive substances and to know the risk factors and protect teenagers from different schools of the area. The methodology is a kind of epidemiological, quantitative, descriptive and cross-sectional study.The research work deals with an epidemiological, descriptive and cross-sectional study, the instrument that was applied was a semi-structured survey, taking as reference the survey of Secretaría Técnica de Drogas with modifications in its variables. The sample comprised of 530 students divided into 250 men and 280 women, which was dazzled that the onset of substance use for the first time out of curiosity, family problems and influences of friendships. In this research it can be evidenced the consumption of alcohol in the male teenagers with a percentage of 60, 00% with more frequency in the ages of 16 and 17 years, the female teenagers corresponds to a 48, 92% with a greater percentage between the Ages 14-15 years, followed by marijuana use with percentages corresponding to 22% in males and in females 6.42% percentages obtained through the investigation.